2018
DOI: 10.1055/a-0752-0217
|View full text |Cite
|
Sign up to set email alerts
|

A High Alanine Aminotransferase/Aspartate Aminotransferase Ratio Determines Insulin Resistance and Metabolically Healthy/Unhealthy Obesity in a General Adult Population in Korea: The Korean National Health and Nutritional Examination Survey 2007–2010

Abstract: Aims Early identification of individuals with insulin resistance (IR) and metabolically unhealthy state can help prevent various diseases and improve quality of life. In this study, we investigated a possible marker of IR and metabolic health status, alanine aminotransferase/aspartate aminotransferase (ALT/AST) ratio, and aimed to confirm its feasibility in a large population study. Methods A total of 16,371 adults from Korean National Health and Examination Survey were studied. Participants were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Some possible reasons may explain why a higher ALT/ AST ratio could easily lead to new-onset NAFLD. (i) A higher ALT/AST ratio has been associated with hepatic fat infiltration and hepatic steatosis [20,21]; (ii) in the Asian population, the ALT/AST ratio was considered to be a reliable marker of insulin resistance (IR) [37,38,42], while IR was a key pathophysiological factor for NAFLD [43]; and (iii) a higher ALT/AST ratio is closely related to inflammation in the liver [24], and chronic inflammation could further induce steatosis and IR in the liver [1,24]. In summary, a higher ALT/AST ratio may lead to chronic inflammation of the liver, IR and steatosis of the liver, which further leads to the occurrence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Some possible reasons may explain why a higher ALT/ AST ratio could easily lead to new-onset NAFLD. (i) A higher ALT/AST ratio has been associated with hepatic fat infiltration and hepatic steatosis [20,21]; (ii) in the Asian population, the ALT/AST ratio was considered to be a reliable marker of insulin resistance (IR) [37,38,42], while IR was a key pathophysiological factor for NAFLD [43]; and (iii) a higher ALT/AST ratio is closely related to inflammation in the liver [24], and chronic inflammation could further induce steatosis and IR in the liver [1,24]. In summary, a higher ALT/AST ratio may lead to chronic inflammation of the liver, IR and steatosis of the liver, which further leads to the occurrence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The change in AST to ALT ratio is not unique to NAFLD. Kwon and Lee (2019) reported that the ratio of AST to ALT correlated with IR A binary logistic regression was performed on ratio of ARA to DGLA and the ratio of AST to ALT. Variables with predicting value were selected by forward likelihood ratio test and the corresponding predicted probability were derived out.…”
Section: Discussionmentioning
confidence: 99%
“…The change in AST to ALT ratio is not unique to NAFLD. Kwon and Lee (2019) reported that the ratio of AST to ALT correlated with IR and metabolically health obesity. The broad association with various diseases may be the reason that the ratio of AST to ALT showed low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In former study, ALT/AST has been brought into evaluate insulin resistance (7,14,15). Hanley et al have informed that ALT/AST could be used for assessing metabolic syndrome through decide insulin sensitivity and acute insulin response (16,17).…”
Section: Discussionmentioning
confidence: 99%